Genetic Comparative Study of Staphyolococcus aureus& Staphylococcus epidermidis Isolated from Wounds, Burns and Skin Flora - Abdul-Kareem, Hala S.; S. Husain, Ali (Iraqi Journal of Science, 2023)
One hundred specimens from wounds, burns, and skin swabs were collectedfrom patients laying and attended to Balad general hospital. It was found that 50isolates belong to Staphylococcus spp., 38 isolates were identified as S. aureus and12 isolates were identified as S. epidermidis according to microscopic, cultural andbiochemical testing. The study of seven extracellular enzyme as virulence factorsincluding the enzymes: urease, lipase, DNase, haemolysin, coagulase, β-lactamase,and lecithinase. Reavealed that 100% of S.aureus had the ability to produce theseenzymes, while S. epidermidis isolates were unable to produce the enzymes DNase,lipase, coagulase, but they were capable to produce haemolysin, urease, lecithinase,and β-lactamase, the range for production of these factors were 58.33 %,80,%, 10,%,and 45% respectively.Eighteen Staphyolococcus isolates were selected according of their ability forproduction most of studies virulence enzymes for detection of genes encoding forthe enzymes heamolysine (hly) and coagulase (coa) by using of polymerase chainreaction (PCR) technique. The Gene hIy was detected in all isolates and coa wasdetected in 14 isolates only.